Acoustic and magnetic properities dependence of restructuring differents magnetic fluids subjected to external magnetic fluid - Regulska, P.; Skumiel, A.; Józefczak, A. (Archives of Acoustics, 2006)
The influence of magnetic field intensity and temperature on acustic and magnetic proprietieswas considered. Measurements were conducted at an ultrasonic wave frequency of3.6 MHz, by a pulse method using the MATEC apparatus. The direction of ultrasonic wavepropagation was parallel to the direction of the external magnetic field. The magnetic fieldrange was 10–150 kA/m. The studies were performed for a selected temperatures. The resultsof this experiments suggested that in magnetic fluids there are different effects connect withrestructuring this fluids.